Pengaruh Literasi Keuangan dan Teknologi Keuangan, melalui Financial Self-Efficacy terhadap Inklusi Keuangan Mahasiswa - Wibowo, Harris Prasetya Cahya; Syah, Muhammad Fahmi Johan (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study highlights the importance of financial literacy and financial technology (fintech) in increasing financial inclusion among college students, as well as how both influence their financial behavior. The study also examines the relationship between self-efficacy and financial management, indicating that an individual's level of confidence in their financial capabilities is considered to influence their financial behavior. With the development of fintech, the accessibility of financial services has also increased, enabling students to save and manage their finances more efficiently. The results indicate that financial literacy and the use of fintech have a significant influence on financial behavior, which in turn contributes to increased financial inclusion. Recommendations emphasize the need to strengthen financial literacy and increase access to financial technology to achieve better financial inclusion in Indonesia.